Emotional and habitual overeating and dietary restrictions in the eating habits of girls and boys - Barbara Janota; Martyna Czapla; Marika Wlazło; Elżbieta Szczepańska (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. Eating habits are mainly shaped at the first stages of human life. Incorrect eating habits in young individuals may in the future lead to eating disorders and predispose to abnormal body weight. Objective. The aim of the study was to investigate eating habits among adolescents and verify whether there are any differences in eating habits between girls and boys. Material and methods. The study was conducted among 337 post-primary school students, including 126 girls and 211 boys. A standardised questionnaire "My eating habits" was used as a research tool. Results. Secret snacking was slightly more common among girls (27.78%) than boys (24.17%). It was also girls who mostly admitted that other people comment on their diet, as indicated by 33.33% of girls and 18.96% of boys. Girls are also more likely to be dissatisfied with their body weight (41.27% vs. 27.49%) and to occasionally avoid eating despite feeling hungry (42.06% vs. 27.01%) compared to boys. Conclusions. The eating habits of young people are mostly varied. There are differences in the d ietary habits of girls and boys; girls are more likely than boys to overeat under the influence of emotions and to apply dietary restrictions to themselves. In order to promote healthy eating habits and support the mental well-being of young people, it is recommended to provide nutritional education and to implement psychological support for those in need.